2005
DOI: 10.1149/1.1915271
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Ellipsometric Study of PEG∕Cl[sup −] Coadsorption on Cu, Ag, and Au

Abstract: Spectroscopic ellipsometry was used to examine the adsorption of poly͑ethylene glycol͒ ͑PEG͒ and Cl − on polycrystalline Cu, Ag, and Au electrodes in sulfuric acid. In halide-free sulfuric acid, PEG adsorption on Cu and Ag is minimal at potentials positive of the estimated potential of zero charge ͑pzc͒. PEG adsorption on Au was also negligible in halide-free environments positive of the pzc, but slight adsorption was evident near the pzc. In contrast, in the presence of adsorbed halide, PEG coadsorption is cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
120
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(135 citation statements)
references
References 32 publications
15
120
0
Order By: Relevance
“…Yet, in the damascene process, PEG is known as an inhibitor. But, it is known this inhibition effect becomes stronger in the presence of Cl -ion in the solution [23][24][25]. In fact, substantially different results are obtained upon the combination of PEG and Cl -into the H 2 SO 4 + CuSO 4 solution.…”
Section: Overpotential Versus Time During the Electroplating Of Cu Frmentioning
confidence: 99%
“…Yet, in the damascene process, PEG is known as an inhibitor. But, it is known this inhibition effect becomes stronger in the presence of Cl -ion in the solution [23][24][25]. In fact, substantially different results are obtained upon the combination of PEG and Cl -into the H 2 SO 4 + CuSO 4 solution.…”
Section: Overpotential Versus Time During the Electroplating Of Cu Frmentioning
confidence: 99%
“…Upon immersion, a PEG layer rapidly forms as a co-adsorbate on top of the halide layer, inhibiting the metal deposition reaction by blocking access of aquo Cu 2 + ions to the Cl --terminated surface. [13,14] A leakage current is associated with local desorption and re-adsorption of PEG ligaments forming the blocking layer. The more dilute SPS species compete for PEG-free surface sites and, once adsorbed, the sulfonate end group of SPS disrupts, displaces, and prevents the readsorption of the PEG layer.…”
Section: Superconformal Cu Electrodepositionmentioning
confidence: 99%
“…On the basis of SERS spectra, complementary modeling of a three-coordination Cu with two ether oxygen ligands from PEG and one chloride ligand is proposed, as illustrated in Figure 27.25b. In contrast to Raman spectroscopy, electrochemical quartz crystal microbalance (EQCM) [86,134] and recent in situ spectroscopic ellipsometry (SE) studies [105,135,136] indicate that Cu ions (neither Cu þ nor Cu 2 þ ) are not essential for the formation of PEG-Cl inhibiting layer. A recent in situ SE study [105] shows that the PEG adsorption alone is very weak and does not vary with the potential, which is consistent with Raman [129] and EQCM [86,134] measurements.…”
Section: Additive Kinetics and Effect On Cu Depositionmentioning
confidence: 99%
“…Studies of electronic properties [105] showed that the PEG-Cl layer does not significantly affect the outer sphere electron-transfer reduction. However, a significant decrease of the interfacial capacitance is observed, which is in agreement with results of electrochemical impedance spectroscopy (EIS) that reported a capacitance reduction to almost a half value upon PEG-Cl layer formation [130].…”
Section: Additive Kinetics and Effect On Cu Depositionmentioning
confidence: 99%
See 1 more Smart Citation